Surface Modifications of Layered Perovskite Oxysulfide Photocatalyst Y2Ti2O5S2 to Enhance Visible‐Light‐Driven Water Splitting - Xizhuang Liang; Junie Jhon M. Vequizo; Lihua Lin; Xiaoping Tao; Qiulian Zhu; Mamiko Nakabayashi; Daling Lu; Hiroaki Yoshida; Akira Yamakata; Takashi Hisatomi; Tsuyoshi Takata; Kazunari Domen (Advanced Science)
Abstract Increasing the efficiency of visible‐light‐driven water splitting systems will require improvements in the charge separation characteristics and redox reaction kinetics associated with narrow‐bandgap photocatalysts. Although the traditional approach of loading a single cocatalyst on selective facets provides reaction sites and reduces the reaction overpotential, pronounced surface charge carrier recombination still results in limited efficiency increases. The present study demonstrates a significant improvement in the hydrogen evolution activity of the layered single‐crystal photocatalyst Y2Ti2O5S2. Increased performance is obtained through sequential loading of Pt cocatalysts using a two‐step process followed by photodeposition of Cr2O3 nanolayers. The stepwise deposition of Pt involved an impregnation‐reduction pretreatment with subsequent photodeposition and produced numerous hydrogen production sites while promoting electron capture. The Cr2O3 shells formed on Pt nanoparticles further promoted electron transfer from the Pt to the water and inhibited surface carrier recombination. Importantly, it is also possible to construct a Z‐scheme overall water splitting system using the optimized Y2Ti2O5S2 in combination with surface‐modified BiVO4 in the presence of [Fe(CN)6]3−/4−, yielding a solar‐to‐hydrogen energy conversion efficiency of 0.19%. This work provides insights into precise surface modifications of narrow‐bandgap photocatalysts as a means of improving the solar water splitting process.